Implementation Management Talent Based on Islamic Values in Improving the Performance of Employees of Islamic Financial Institutions - abdul wahid; Ahmad Zainul Abidin; Muhammad Syafi'i Budi Santoso (LPPM STIES BABUSSALAM, 2026)
Study This aim For analyze implementation management talent based Islamic values in increase performance employees at the institution Islamic finance . Management talent is one of the important strategies in management source Power man For acquire , develop , maintain , and optimize potential employees to be able to give contribution maximum to achievement objective organization . In Islamic perspective , implementation management talent No only oriented towards competence and productivity , but also emphasizes values trustworthy , ihsan , siddiq , fathanah , tabligh , justice , and professionalism as runway in operate work . Research This use approach qualitative with method studies case in one of the institution Islamic finance . Data obtained through interview in-depth , observation , and documentation , then analyzed use technique interactive data analysis that includes data reduction , data presentation , and data extraction conclusion . Research result show that implementation management talent based Islamic values have implemented through a recruitment process that takes into account competence and integrity Islam , training and development programs spiritually based , system evaluation integrated performance​ aspect professional and moral, as well as giving awards that encourage improvement motivation work . Implementation Islamic values in every stages management talent proven capable increase competence , commitment , loyalty , discipline , and productivity employee so that impact positive to improvement quality service and performance organization in a way overall . Therefore that , integration between practice management modern talent with Islamic values become an effective strategy in create source Power superior , integrated and empowered human beings competition in institutions Islamic finance